2023
DOI: 10.7759/cureus.46880
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Site Infections Following Fasciotomy in Patients With Acute Compartment Syndrome: A Study on the February 2023 Kahramanmaraş Earthquake

Erkan Akgun,
Abdulsamet Emet,
Kemal Sibar
et al.

Abstract: Introduction: Surgical site infections (SSIs) developing after fasciotomy are difficult to treat, costly, and an important source of mortality and morbidity. This study aimed to determine the risk factors affecting the development of SSI in patients who underwent fasciotomy with the diagnosis of acute compartment syndrome (ACS) within 72 hours after two consecutive earthquakes of 7.7 and 7.6 magnitude that occurred in Kahramanmaraş on February 6, 2023. Method: A total of 116 patients were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…In another study, again similar to ours, exposure to a collapse, fasciotomy, and amputation were more common in patients with WI [ 7 ]. In a study evaluating the risk of SSI in patients with multiple extremity damage or bone fractures, no increase in the risk of infection was found [ 19 ]. We did not find a relationship between the presence of fracture and WI, but WI was more common in cases with damage to multiple extremities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In another study, again similar to ours, exposure to a collapse, fasciotomy, and amputation were more common in patients with WI [ 7 ]. In a study evaluating the risk of SSI in patients with multiple extremity damage or bone fractures, no increase in the risk of infection was found [ 19 ]. We did not find a relationship between the presence of fracture and WI, but WI was more common in cases with damage to multiple extremities.…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating SSIs in patients who underwent fasciotomy due to earthquake injuries, renal insufficiency was found to be associated with infection [ 19 ]. In our study, patients with renal insufficiency were included in the group with crush syndrome and it was found that WI developed more frequently among these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations